(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Anas, Damayanti F, Kadapi M, Carsono N, Sari S. 2022. The shifting genetic diversity pattern of Indonesian rice improved varieties from 1943-2019 based on historical pedigree data. Biodiversitas 23: 4649-4656. For rice plants in Indonesia, stagnation in increasing crop yields due to a reduction in genetic diversity is a significant issue. The issue of using the same parents in breeding programs and consumer preferences for a single main variety are among the causes of the narrowing of rice plants’ genetic diversity. The purpose of this study is to figure out which ancestors are significant and how the genetic diversity of improved Indonesian rice cultivars has changed over time. Changes in the genetic background of the Indonesian rice gene pool were decided using pedigree analysis by calculating the coefficient of parentage (COP) among varieties. There are 280 ancestors in the rice gene pool. The pedigree map exemplifies the complexities of rice breeding in Indonesia. The four classical ancestors of DGWG, Taichung Native1, China, and Latisail had a noteworthy influence on all irrigated rice plant types (11.22%) and upland rice plant types (8.30%) in the gene pool. The dominance of the phenomenal variety IR64 has been continued by Inpari 32, which is a direct derivative of Ciherang. In the meantime, Inpago9, Luhur 2, and UPLRI ancestors set the foundation for the upland rice plant type. Inpara7 and Inpara9, along with their IRRI-introduced parents (IRRIpara4 and IRRIpara5), had a significant impact on Indonesian tidal rice plants. The A1, Hipa7, and Hipa3 varieties are heavily influenced by the hybrid rice plants of Indonesia.